2017
DOI: 10.17957/tpmj/17.3930
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Ectasia; Prevalence and Clinical Characteristics: Experience From a Single Cardiac Center

Abstract: ABSTRACT… Background: Coronary artery ectasia (CAE) is well-recognized but relatively uncommon finding during diagnostic coronary angiography. Coronary artery ectasia is defined as a segment of coronary artery that is 1.5 times more dilated in diameter than the nearby segments. Its clinical presentations are unstable angina, coronary vasospasm, and acute myocardial infarction. Objectives: To determine the clinical characteristics, presentation and treatment in patients with documented coronary artery ectasia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…19 Recently, Ali et al reported that about 41.7% of patients diagnosed with CAE had diabetes. 20 Therefore, it was extremely important to study the spectrum of CAE in the diabetic population of our local population diagnosed with CAE on angiography. As per our study findings, no statistically significant difference (p-value<0.05) was shown with respect to the severity of disease in diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 Recently, Ali et al reported that about 41.7% of patients diagnosed with CAE had diabetes. 20 Therefore, it was extremely important to study the spectrum of CAE in the diabetic population of our local population diagnosed with CAE on angiography. As per our study findings, no statistically significant difference (p-value<0.05) was shown with respect to the severity of disease in diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…La patogenia no ha sido del todo dilucidada, pero por el momento, se apunta al accionar del óxido nítrico (NO) de manera crónica, en el endotelio coronario (Alkhouli y Nunez Gil 2019), como lo demostró un estudio estadounidense realizado en veteranos de guerra en Vietnam, con ectasia coronaria, que estuvieron expuestos al 'agente naranja' (herbicida utilizado como arma química) (Dwyer y Flesch-Janys 1995), en el que se sugiere que la exposición prolongada estimula la producción de acetilcolina, que a su vez causa sobreestimulación de NO y adelgazamiento de la íntima media coronaria (Malviya et al 2017). Las manifestaciones clínicas son variables, suele cursar con angina estable, y en peculiares ocasiones con angina inestable, especialmente por reflujo retrógrado y lento de la arteria ectásica u oclusión parcial del segmento ectásico por la dinámica trombogénica del flujo (Ali et al 2017), factor implicado en el infarto de miocardio sin elevación del ST, y en ocasiones, del infarto con ST elevado, por lo que no es raro el síndrome coronario agudo (SCA) en estos pacientes (Papadakis et al 2001).…”
Section: Introductionunclassified